Exploring the Nexus Between Fundamental Strength and Market Value in Energy Companies: Evidence From Environmental, Social, and Corporate Governance Perspective in Poland - Tarczynska-Luniewska, Malgorzata; Flaga-Gieruszynska, Kinga; Ankiewicz, Magda (Frontiers in Energy Research, 2022)
Sustainable development is an important element of the interests of modern economics. In order to function on the market and develop, companies must adhere to the principles of sustainable development. In this context, the interest of companies in the implementation and application of ESG strategies is growing. In the long-term perspective, the use of this type of strategy is to generate an increase in the company's value. This value is of interest to the company's stakeholders, who may use the information about the company's value, e.g., in terms of its management or investment. The aim of the article is to examine the relationship between the company's value and its fundamental strength. The analysis covers companies from the energy sector (listed on the Warsaw Stock Exchange) that declare the use of ESG practices. The time range of the research covers the years 2013 - 2020. For the purpose of the study, selected statistical measures and the Fundamental Power Index (FPI) were used. This indicator synthetically evaluates all areas of the company's operations. The results of the research show that the value of the company is not influenced by its fundamental strength. Therefore, the investors do not reduce the company's value in the light of information on its fundamental strength. In addition, companies vary in terms of fundamental strength measured by FPI.